Neurosurgical Treatment and Outcome of Pediatric Skull Base Lesions: A Case Series and Review of the Literature - Ladina Greuter; Tim Hallenberger; Raphael Guzman; Jehuda Soleman (MDPI AG, 2023)
Introduction: Pediatric skull base lesions occur rarely and are of various etiologies. Traditionally, open craniotomy has been the treatment of choice; however, nowadays, endoscopic approaches are increasingly applied. In this retrospective case series, we describe our experience in treating pediatric skull base lesions and provide a systematic overview of the literature on the treatment and outcome of pediatric skull base lesions. Methods: We conducted a retrospective data collection of all pediatric patients (<18 years) treated for a skull base lesion at the Division of Pediatric Neurosurgery, University Children's Hospital Basel, Switzerland, between 2015 and 2021. Descriptive statistics and a systematic review of the available literature were additionally conducted. Results: We included 17 patients with a mean age of 8.92 (±5.76) years and nine males (52.9%). The most common entity was sellar pathologies (n = 8 47.1%), with craniopharyngioma being the most common pathology (n = 4, 23.5%). Endoscopic approaches, either endonasal transsphenoidal or transventricular, were used in nine (52.9%) cases. Six patients (35.3%) suffered from transient postoperative complications, while in none of the patients these were permanent. Of the nine (52.9%) patients with preoperative deficits, two (11.8%) showed complete recovery and one (5.9%) partial recovery after surgery. After screening 363 articles, we included 16 studies with a total of 807 patients for the systematic review. The most common pathology reported in the literature confirmed our finding of craniopharyngioma (n = 142, 18.0%). The mean PFS amongst all the studies included was 37.73 (95% CI [36.2, 39.2]) months, and the overall weighted complication rate was 40% (95% CI [0.28 to 0.53] with a permanent complication rate of 15% (95% CI [0.08 to 0.27]. Only one study reported an overall survival of their cohort of 68% at five years. Conclusion: This study highlights the rarity and heterogeneity of skull base lesions in the pediatric population. While these pathologies are often benign, achieving GTR is challenging due to the deep localization of the lesions and eloquent adjacent structures, leading to high complication rates. Therefore, skull base lesions in children require an experienced multidisciplinary team to provide optimal care.